Influence of Adding Empagliflozin to Conventional Anti-diabetic Therapy on Quality of Life Scale for Type 2 Diabetic Patients - Hadeel Delman Najim; Mohammed Mahmood Mohammed; Abbas Mahdi Rahmah (Iraqi Journal of Pharmaceutical Sciences, 2024)
To evaluate the efficacy of empagliflozin on the quality of life (QoL) and glycemic index in patients with type 2 diabetes mellitus (T2DM) inadequately controlled with conventional oral anti-diabetic agents (OADs).A pre-post study involved forty T2DM patients who were on a combination of three OADs (glimepiride + metformin + vildagliptin) with glycated hemoglobin A1c (HbA1c) 7.0% - 12.0%. All patients received empagliflozin (10 mg/day) as add-on therapy for 16 weeks.Adding empagliflozin showed significant reduction in postprandial plasma glucose (PPG), (HbA1c), body mass index (BMI) and index of central obesity (ICO) (p<0.001). Significant improvements have been shown in the Quality of Life in Iraqi type 2 diabetic patients (QOLSID) scores post-intervention (p<0.001). Besides, good QoL was reported in patients with lower BMI and among those who had DM for duration less than 10 years.The outcome of this study showed that empagliflozin as add-on to oral antidiabetic triple therapy in poorly controlled T2DM has achieved a better weight management, well glycaemic control and enhanced QoL through the therapy, and was well tolerated among the study sample.Keywords: Empagliflozin, Glycemic index, Quality of life, SGLT2 inhibitors, Type 2 DM.